Challenges in Environmental of Electrical Appliances: Consumer Perception of Environmentally-friendly Products and Appliance Testing for Energy Label Accuracy - Knošková, Ľubica, 1965-
Spotrebiteľské vnímanie ekologicky prijateľných produktov.Testovanie elektických spotrebičov.